Do Workplace Spirituality and Emotional Intelligence Have A Role in Enhancing Affective Commitment for Millenials? - Wahyu Saripudin; Asep Kurnia (Department of Management - Institut Shanti Bhuana, 2021)
This study aims to examine the role of workplace spirituality in enhancing affective commitment with emotional intelligence as a moderating variable. The respondents in this research are the millennial generation who work in various industrial sectors in west Java. This study applies a quantitative method and the survey method is used for collecting data.. The number of respondents obtained as many as 203 respondents who have worked for at least 1 year and were born in the range of 1980-2000. Methods of data analysis using simple linear regression and moderated regression analysis (MRA). The results reveal that workplace spirituality had a significant positive effect on affective commitment and emotional intelligence did not moderate the relationship between them.